Propargyl/methyl furanosides as potential glycosyl donors - Vidadala, Srinivasa Rao; Gayatri, Gaddamannugu; Sastry, G. Narahari; Hotha, Srinivas (Chemical Communications, 2011)
Transfuranosylations are not well studied though many similar studies exist for transpyranosylation; herein, we report that propargyl/methyl D-ribf- and D-lyxf- give only 1,2-trans glycosides whereas D-araf- and D-xylf- result in a mixture of 1,2-trans and 1,2-cis glycosides; observed facts are rationalised by computational studies.